Discrimination against equal men in the labor market - Viana, Hyalle Abreu (2020)
The objective of this thesis is to investigate how we react to men who defend gender equality, who in this thesis were called egalitarian men. To achieve this objective, this thesis is organized in two articles. In the first article, two studies were developed. Study 1 (N = 250) investigated the attribution of stereotypes to egalitarian men through an open question, and study 2 (N = 221) analyzed the stereotypical attribution to egalitarian men and women in a work context considered to be male. Taken together, the results of this article show that the egalitarian man is perceived as fragile and possibly homosexual. But on the other hand, he is perceived as more competent than traditional men. The second article, through two studies, investigated discrimination against equal men in the labor market. Thus, Study 1 (N = 235) tested the hypothesis that a man's egalitarian or traditional positioning in relation to the division of gender roles influences the agreement of his hiring / failing for a leadership position. The role of sexism in the relationship between the type of positioning of men (traditional X egalitarian) and the decision made by the recruiter in a selective process (hiring or not) in the perception of the legitimacy of this decision was also analyzed. Study 2 (N = 278), in turn, analyzed what types of justifications people use to agree or disagree with hiring / failing egalitarian or traditional candidates. The results of these two studies showed that the more one adheres to hostile sexism, the greater the perceived legitimacy in hiring the traditional candidate. Regarding the justifications, we found that the hiring of the traditional candidate is justified by his dedication to the job and his rejction by the fact of being dependent on his wife. The hiring of the egalitarian candidate is justified because he seems to be a good professional and his rejection for his priority given to the family. Together, the results presented in this thesis show the diverse faces that sexism can take on Brazilian society.